Risk Factors for Post-Thrombotic Syndrome in Patients With a First Proximal Deep Venous Thrombosis Treated With Direct Oral Anticoagulants. (August 2022) - Spiezia, Luca; Campello, Elena; Simion, Chiara; Poretto, Anna; Dalla Valle, Fabio; Simioni, Paolo
The incidence of post-thrombotic syndrome (PTS) in patients with deep vein thrombosis (DVT) treated with direct oral anticoagulants (DOACs) remains a matter of debate. Hence, our endeavor to investigate a large cohort of patients with a first episode of proximal DVT treated with DOACs to ascertain the incidence and predisposing risk factors for PTS. All consecutive patients referred to the Thrombotic and Haemorrhagic Diseases Unit of Padova University Hospital (Italy) between January 2014 and January 2018 for a first episode of proximal DVT were considered for enrollment. Participants received DOACs for a minimum period of 3 months. PTS was assessed using the Villalta score up to 36 months after DVT diagnosis. Among 769 enrolled patients (M/F 353/416, age range 26–87 years), 152 (19.8%) developed PTS and 30 (3.9%) developed severe PTS. The adjusted hazard ratio was significant for obesity (1.64, 95% CI 1.28–2.39) and DVT site (femoral and/or iliac veins vs popliteal vein) (1.23, 95% CI 1.15–3.00). The incidence of PTS is not negligible in patients with proximal DVT despite the use of DOACs. We identified obesity and iliofemoral DVT as possible risk factors for PTS. Larger prospective studies are needed to confirm our findings and optimize therapeutic strategies.